Enough with Color-blind Classrooms! Giving African-American Students a Voice in Constructing Their Learning Experience - Jacqueline P. Callery (Adult Education Research Conference, 2008)
Literature on critical thinking discussing the experiences of African American students is limited. This study examined the experiences of African American undergraduate business students, as they became stronger critical thinkers. The study concludes by suggesting educators in higher education settings embrace the cultural diversity of the students in their classroom to inform culturally relevant course content development.
Keywords: African American; color-blind; critical race theory; culturally relevant pedagogy